The Function of Educators in Expanding their Professional Competence through Exploration - Yan, Pan; Natarajan, Babu (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Examining how actively teachers participate in inquiry-based professional development is the goal of this qualitative study. The research used classroom observations and in-depth interviews to investigate teachers' viewpoints, experiences, and difficulties with professional development programs. The main focuses of the study are their level of participation and their perception of its impact on classroom learning. Schools that value research aim to develop reflective practitioners among their faculty by making research and an inquiry-based pedagogy integral parts of their curricula. A lack of data about the academic and personal success of program alums is a major drawback. This research sought to evaluate the development of inquiry-based practice among seven first-year teachers from Dutch academic teacher training programs. For three years, these grads and their school administrators were subjected to questioning. Their level of engagement with the curriculum increases as the school and students go through inquiry-based learning. It has been suggested by scholars that inquiry-based learning might have many interesting benefits for educators. While obstacles like time and reluctance to change persist, the findings demonstrate that inquiry-based professional development fosters collaboration and self-reflection. The findings might provide valuable information for future professional development (PD) programs that aim to increase student achievement via increased teacher engagement and the use of inquiry-based teaching methods.